The Effectiveness of Administering Pure Honey on Increasing Hemoglobin in Adolescent Girls in Sibangkaja Village - Ni Made Surya Dewi; Luh Putu Widiastini; Putu Ayu Dina Saraswati (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
Anemia defined as a condition in when the count of body's red blood cell’s lower than normal. Teenagers can overcome anemia naturally, by drinking honey. This study aimed to investigate the effectiveness of administering pure honey to improve hemoglobin in adolescent. This study was quasi-experimental design with pretest and post-test control group. Samples was 36 respondents (18 respondents for each control group and treatment group) which determined by total sampling technique. The research was conducted in November-December 2023. The data collection technique included pretest and post-test questionnaires for both groups, Haemoglobin (Hb) sticks was used to measure the Hb levels. Data analysis included descriptive analysis, and comparison analysis using the Wilcoxon and Mann Whitney tests. The study's findings revealed that before the intervention, both groups had anemia. The study yielded a z- value of -3.429 and p-value of 0.001 (p<0.05). Administering pure honey to young women had been shown increase hemoglobin levels. The findings will be utilized to propose midwifery services as a non-pharmacological method of reducing anemia in teenagers, particularly young women.